The Effect of Academic Self-Efficacy on Students’ Thesis Writing Resilience - Sasferi, Nuzmi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
The most crucial inventory of literacy skills for students is completing a final project in the form of a thesis. However, many students experience high levels of anxiety during the guidance process, due to worries about conducting difficult research and demands from parents, as well as finding problems that can be used as titles, understanding how to write scientific papers, finding references, and meeting supervisors. This leads to stress among students, who feel pressured and lack confidence in their abilities, which is an important phenomenon studied here. Therefore, this study aims to determine the influence of student self-efficacy factors on their ability to complete their thesis. This research is a form of correlation between student self-efficacy and the ability to write a thesis, and it involved 117 seventh-semester students of the Islamic Religious Education study program at one of the Islamic universities in Jambi, Indonesia. The study used a Thesis Writing Resilience questionnaire consisting of 43 items and an Academic Self-Efficacy questionnaire consisting of 35 items. The study found a strong correlation between self-efficacy and the ability to complete a thesis with a correlation coefficient of -0.8. Therefore, there is a strong influence of student self-efficacy on their ability to write a thesis. Self-efficacy can reduce or decrease student anxiety in preparing a thesis. This level of academic self-efficacy is more influenced by the level of individual resilience to their beliefs and individual ability to master a task. By improving student self-efficacy, students can feel more confident and less anxious in the thesis writing process. Therefore, universities and educators should develop interventions to improve student self-efficacy, such as providing guidance and support to help students develop the necessary skills to complete their thesis successfully. Additionally, future research should explore other factors that may influence student self-efficacy, such as family support, cultural backgrounds, and personal motivation, to gain a more comprehensive understanding of the topic.